Potential biomarkers for early detection of diabetic kidney disease. (March 2020) - Hussain, Salman; Habib, Anwar; Hussain, Md Sarfaraj; Najmi, Abul Kalam
Highlights: An inverse correlation was observed between eGFR and galectin-3 and the GDF-15 plasma level. Levels of biomarkers increases as the kidney function worsens. ROC curve confirms the potential of galectin-3 and GDF-15 as a biomarker of DKD. Abstract: Introduction: To assess the potential of galectin-3 and growth differentiation factor-15 (GDF-15) biomarkers for the early detection of diabetic kidney disease (DKD). Methodology: This was a cross-sectional study conducted over a period of 1.2 years. Patients were stratified based on estimated glomerular filtration rate (eGFR) and albuminuria level. The receiver operating characteristic (ROC) curve was plotted to assess the diagnostic potential of biomarkers. Results: A total of 90 patients included in this study. Patients were grouped as normoalbuminuria (30 patients), microalbuminuria (30 patients), and macroalbuminuria (30 patients). Galectin-3 and GDF-15 levels were significantly elevated in T2DM patients with macroalbuminuria ( p = <0.05). Higher levels of galectin-3 and GDF-15 were found in patients with poor kidney function (Stage IV-V CKD). Negative correlation was observed between galectin- 3 (r = −0.472) and eGFR (p = 0.000), GDF-15 (r = −0.917) and eGFR ( p  <0.000). The ROC analysis yielded an area under curve (AUC) of 0.776 (95% CI: 0.677 to 0.875; p = <0.0001) for galectin-3 and an AUC of 0.963 (95% CI: 0.929 to 0.997; p = <0.0001) for GDF-15. Conclusion: In DKD patients the galectin-3 and GDF-15 levels were inversely related to the eGFR which was further confirmed by the ROC curve demonstrating the potential of galectin-3 and GDF-15 as a biomarker.